2018
DOI: 10.1177/1559325818800153
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of the Protein Expression of Cox2, NFκB, and STAT-3 by Some Antioxidants in the Liver of Sodium Fluoride–Intoxicated Rats

Abstract: The present study aimed to explore the efficiency of N-acetyl cysteine (NACC) or thymoquinone (TMQ) alone or in combination in the downregulation of inflammatory molecule expression and decreasing hepatic injury in response to sodium fluoride (SF). Sodium fluoride upregulated serum alanine and aspartate transferases activities, tumor necrosis factor α and hepatic malondialdehyde and nitric oxide levels, and the expression of cyclooxygenase 2, nuclear factor κB cell, and signal transducer and activator of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Research suggests that inhibiting the expression of STAT1 signaling pathway can inhibit the production of IP-10/CXCL 10 induced by IFN-γ in orbital fibroblasts of patients with TAO, thereby alleviating orbital inflammation [29]. The STAT3 signaling pathway might play an anti-inflammatory, antioxidant, and immunomodulatory role in chronic respiratory diseases, breast cancer, and liver inflammation [3032]. Inflammation and oxidative stress damage to orbital tissue is the main pathogenesis of TAO [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that inhibiting the expression of STAT1 signaling pathway can inhibit the production of IP-10/CXCL 10 induced by IFN-γ in orbital fibroblasts of patients with TAO, thereby alleviating orbital inflammation [29]. The STAT3 signaling pathway might play an anti-inflammatory, antioxidant, and immunomodulatory role in chronic respiratory diseases, breast cancer, and liver inflammation [3032]. Inflammation and oxidative stress damage to orbital tissue is the main pathogenesis of TAO [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in the activities of aminotransferases in present study might be due to oxidative stress generated by sodium fluoride which could alter the membrane permeability of hepatocytes in rats treated with 300 and 600 mg/L NaF. Fluoride toxicity induced oxidative damage leads to liver dysfunction and deformities in the levels of serum biomarker transaminases [42]. A marked increase in the activity of ALT was attributed to a change in the permeability of the hepatic cell membrane [43].…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have demonstrated that hepatocyte death through mechanisms including apoptosis, necrosis and autophagy, serves a crucial role in septic liver injury (3)(4)(5). The death of vast numbers of hepatocytes leads to elevated levels of AST and ALT and subsequent liver failure (7).…”
Section: Discussionmentioning
confidence: 99%
“…During sepsis, inflammatory cytokines released from immune cells bind to receptors on hepatocytes and induce the activation of downstream signaling, resulting in the apoptosis or necrosis of hepatocytes (4)(5)(6). Previous studies identified inflammasome activation in hepatocytes as a major cause of hepatocyte cell death and of septic liver injury and failure (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%